2017
DOI: 10.1186/s13578-017-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of gene expression through the nonsense-mediated RNA decay pathway

Abstract: Nonsense-mediated RNA decay (NMD) was originally discovered as a cellular surveillance pathway that safeguards the quality of mRNA transcripts in eukaryotic cells. In its canonical function, NMD prevents translation of mutant mRNAs harboring premature termination codons (PTCs) by targeting them for degradation. However, recent studies have shown that NMD has a much broader role in gene expression by regulating the stability of many normal transcripts. In this review, we discuss the function of NMD in normal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 179 publications
8
118
0
Order By: Relevance
“…The precise regulation of genetic information, as it is passed from gene to transcript to protein, is crucial for the survival of cells and organisms. From a single gene, multiple mature messenger RNA (mRNA) transcripts arise through alternative pre-mRNA, resulting in mature species with differences in both the coding and non-coding regions [1]. Even beyond the end-points of mRNA transcription, the quality and quantity of mRNAs in cells is tightly controlled through various pathways [2].…”
Section: The Nonsense-mediated Mrna Decay (Nmd) Pathway and Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…The precise regulation of genetic information, as it is passed from gene to transcript to protein, is crucial for the survival of cells and organisms. From a single gene, multiple mature messenger RNA (mRNA) transcripts arise through alternative pre-mRNA, resulting in mature species with differences in both the coding and non-coding regions [1]. Even beyond the end-points of mRNA transcription, the quality and quantity of mRNAs in cells is tightly controlled through various pathways [2].…”
Section: The Nonsense-mediated Mrna Decay (Nmd) Pathway and Machinerymentioning
confidence: 99%
“…However in humans, RNAi-based knockdowns on NMD genes showed that this pathway plays a crucial role in cell cycle regulation [48], cell viability [49] and the response to amino acid starvation [50]. Furthermore, NMD components have NMD-independent functions, such as the DNA damage response [51], maintenance of the telomere integrity [48], regulation of calcium metabolism [1], viral infection, replication [52] and tumourigenesis.…”
Section: Nmd In the Maintenance And Homeostasis Of The Cellmentioning
confidence: 99%
“…The increased skipping of exon 3 (out of 5) associated with the minor haplotype results in more transcripts with a frameshift and a premature termination codon (PTC) near the 5' end of exon 4. Many mammalian transcripts with PTCs are subject to nonsense-mediated decay (NMD), particularly when the PTC is not located in the last exon 67 . Treatment of cells with protein synthesis inhibitors such as cycloheximide (CHX) has been shown to increase the abundance of transcripts subject to NMD 68 .…”
Section: Fine Mapping Of Complex Ocular Disease Risk Locimentioning
confidence: 99%
“…NMD was originally discovered through its role as a quality control mechanism that degrades aberrant mRNAs harboring premature termination codons generated by mutations, errors in splicing, and programmed gene rearrangements (Fig 1A;Nickless et al, 2017). Subsequently, NMD was found to also degrade subsets of normal mRNAs with stop codons in specific contexts.…”
mentioning
confidence: 99%
“…Increasing evidence suggests that the ability of NMD to degrade specific normal mRNAs is regulated and critical for a variety of functions ranging from differentiation and development to stress responses and autophagy. For example, NMD degrades the mRNA encoding the pro-apoptotic protein, GADD45, to allow for normal early fly development; NMD degrades Smad7 mRNA to promote selfrenewal of neural stem cells; and NMD degrades IRE1a mRNA to shape the unfolded protein stress response (Karam et al, 2013;Nickless et al, 2017).…”
mentioning
confidence: 99%